Loss of ARID1A induces a stemness gene ALDH1A1 expression with histone acetylation in the malignant subtype of cholangiocarcinoma. (30th October 2019) - Yoshino, Jun; Akiyama, Yoshimitsu; Shimada, Shu; Ogura, Toshiro; Ogawa, Kosuke; Ono, Hiroaki; Mitsunori, Yusuke; Ban, Daisuke; Kudo, Atsushi; Yamaoka, Shoji; Tanabe, Minoru; Tanaka, Shinji
Abstract: Genomic analyses have recently discovered the malignant subtype of human intrahepatic cholangiocarcinoma (ICC) characterized by frequent mutations of chromatin remodeling gene ARID1A ; however, the biological and molecular functions still remain obscure. We here examined the clinical and biological significances of ARID1A deficiency in human ICC. Immunohistochemical analysis demonstrated that the loss of ARID1A was an independent prognostic factor for overall survival of ICC patients ( P = 0.023). We established ARID1A -knockout (KO) cells by using the CRISPR/Cas9 system from two human cholangiocarcinoma cell lines. ARID1A -KO cells exhibited significantly enhanced migration, invasion, and sphere formation activity. Microarray analysis revealed that ALDH1A1, a stemness gene, was the most significantly elevated genes in ARID1A -KO cells. In addition, ALDH enzymatic activity as a hallmark of cancer stem cells was markedly high in the KO cells. ARID1A and histone deacetylase 1 were directly recruited to the ALDH1A1 promoter region in cholangiocarcinoma cells with undetectable ALDH1A1 expression by chromatin immunoprecipitation assay. The histone H3K27 acetylation level at the ALDH1A1 promoter region was increased in cells when ARID1A was disrupted ( P < 0.01). Clinically, inverse correlation between ARID1A and ALDH1A1 expression was also identified in primary ICC ( P = 0.018), and ARID1A-negative and ALDH1A1-positve ICCs showed worse prognosis than only ARID1A-negative cases ( P = 0.002). In conclusion, ARID1A may function as a tumor suppressor in ICC through transcriptional downregulation of ALDH1A1 expression with decreasing histone H3K27 acetylation. Our studies provide the basis for the development of new epigenetic approaches to ARID1A-negative ICC. Immunohistochemical loss of ARID1A is an independent prognostic factor in intrahepatic cholangiocarcinoma patients. ARID1A recruits HDAC1 to the promoter region of ALDH1A1, a stemness gene, and epigenetically suppresses ALDH1A1 expression with decreasing histone H3K27 acetylation in cholangiocarcinoma cells.